The impact of listed companies’ participation in targeted poverty alleviation on financing constraints: Mediating effect based on policy resources - Huo, Zenghui; Xia, Yufei; Liu, Ding; Zhang, Mei (Frontiers in Environmental Science, 2023)
This article aims to explore the inner relationship between targeted poverty alleviation and financing constraints of listed companies, and further reveal the underlying impact mechanism. Based on the data of listed companies in Shanghai and Shenzhen A-share main board participating in targeted poverty alleviation from 2017 to 2020, graded response models and mediation models are conducted. From the perspective of resource motivation, the study examined the relationship between the investment in targeted poverty alleviation and financing constraints of listed companies and introduces policy resources as mediator variable to reveal the underlying mechanism. The study found that the participation of listed companies in targeted poverty alleviation can significantly ease financing constraints, and policy resources can play an intermediary effect in the process. For enterprises with different equity nature, in state-owned enterprises, policy resources play a small intermediary role between poverty alleviation inputs and financing constraints. Meanwhile, in non-state-owned enterprises, government subsidies play a significant intermediary role, and tax incentives play a small intermediary role. In response to this, policy suggestions such as improving the disclosure of poverty alleviation information, expanding policy preferences, and increasing poverty alleviation subsidies have been suggested.